Understanding Pornography Addiction in India: Insights from a Retrospective, Observational Study - Neeharika Jaiswal; Sandip Deshpande; Nikunj Gokani; Ashima Sahore; Tanha Gowande (BJPsych Open)
Aims: This study examines the demographic factors and severity of pornography addiction in India, analysing the impact of age, relationship status, co-morbid conditions, and socio-cultural norms on addiction patterns and treatment outcomes.